Analisis Pemecahan Masalah Siswa pada Materi Kesetimbangan Benda Tegar - Susilawati Susilawati; Siti Nurdianti Muhajir; Resti Warliani (Universitas Garut, 2025)
The aim of this study is to investigate students’ problem-solving ability in learning the topic of rigid body equilibrium. The indicators of problem-solving ability used in this research are based on Heller’s problem-solving framework, namely: (1) understanding the problem, (2) describing the problem in terms of physics concepts, (3) planning a solution, (4) implementing the solution, and (5) evaluating the solution. The research method employed is descriptive quantitative, using a single-case design, that is, a case study focusing on only one unit of analysis. The participants in this study were Year 11 science-stream students (class XI MIA) at an Islamic upper secondary school (MA) in Garut Regency. Data were collected through problem-solving tests, interviews, and learner worksheets (LKPD). The findings indicate that students’ problem-solving abilities fall into varied categories with an overall mean in the moderate range. Nevertheless, the results suggest that improvements in teaching methods that better support problem-solving skills are still required.